Solubility of Carbamazepine Co-Crystals in Ethanolic Solution - Noor Ashila, Ramle; Syarifah, Abd Rahim; Nornizar, Anuar; El-Hadad, Omar (AIP Publishing, 2017)
The study aimed to determine the solubility of carbamazepine (CBZ) co-crystals formed from co-crystal formers (CCFs) of nicotinamide (NIC), saccharin (SAC), succinic acid (SUC) and fumaric acid (FUM) at various temperatures (25-50°C). High Performance Liquid Chromatography (HPLC) was used to determine the solubility and the X-Ray Powder Diffraction was used to characterize the crystals. The solubility of CBZ-NIC and CBZ-FUM co-crystals were found to be higher than the solubility of the CBZ for the range of studied temperatures. However, opposite findings was obtained for CBZ-SUC co-crystal as its solubility is lower than the solubility of CBZ. Different trend was found for CBZ-SAC co-crystal in which for temperature lower than 40°C, the solubility of CBZ crystal is higher than the CBZSAC co-crystal. The solubility of CBZ-SAC co-crystal is higher than the solubility of CBZ at a temperature above 40°C. CBZ co-crystals with NIC and FUM have shown to increase the solubility of CBZ by solubility ratio of 1.95 and 1.24 respectively. However, the CBZ co-crystal with SAC was found to have similar solubility value as the CBZ.